1974
DOI: 10.1149/1.2401717
|View full text |Cite
|
Sign up to set email alerts
|

Optical Investigation of Different Silicon Films

Abstract: In the case of weak absorption, the spectral reflectance of a thin film on a nonabsorbing substrate can be used to determine the spectral dependence of the absorption constant. For this purpose, a relatively simple method is described evaluating the envelopes of the interference extrema. This method as well as a Kramers-Kronig analysis were applied to epitaxial, polycrystalline, and amorphous silicon films in the energy range 0.5-5.5 eV. With decreasing crystal quality, changes in the spectral dependence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Kiihl et al [14] have shown differences in the optical constants of epitaxial, polycrystalline , and amorphous silicon in the energy range 0.5 to 5.5 eV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kiihl et al [14] have shown differences in the optical constants of epitaxial, polycrystalline , and amorphous silicon in the energy range 0.5 to 5.5 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation of SOS device channel current with infrared reflectance data for corresponding sapphire substrates 12 Figure 6. Correlation of gated-Hall mobility of SOS structures with infrared reflectance data of corresponding sapphire substrates 13 Figure 7. Correlation of SOS device channel current with ultraviolet reflectance data for corresponding epitaxial silicon films 14 Figure 8. Correlation of gated-Hall mobility of SOS structures with ultraviolet reflectance data of corresponding epitaxial silicon films 15 Figure 9.…”
mentioning
confidence: 99%